The Steinhaus-Weil Property: II. The Simmons-Mospan Converse - Bingham, Nicholas H.; Ostaszewski, Adam J. (Sarajevo Journal of Mathematics, 2022)
In this second part of a four-part series (with Parts I, III, IV referring to [BinO4,5,6]), we develop (via Propositions 1, 2 and Theorems 1, 2) a number of relatives of the Simmons-Mospan theorem, a converse to the Steinhaus-Weil theorem (for another, see [BinO1], and for yet others [BinO3, §8.5]). In Part III [BinO5, Theorems 1, 2], we link this with topologies of Weil type.